2012
DOI: 10.1007/s10661-012-2898-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic activities on water quality of Lidder River in Kashmir Himalayas

Abstract: The pristine waters of Kashmir Himalaya are showing signs of deterioration due to multiple reasons. This study researches the causes of deteriorating water quality in the Lidder River, one of the main tributaries of Jhelum River in Kashmir Himalaya. The land use and land cover of the Lidder catchment were generated using multi-spectral, bi-seasonal IRS LISS III (October 2005 and May 2006) satellite data to identify the extent of agriculture and horticulture lands that are the main non-point sources of pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 23 publications
1
53
0
1
Order By: Relevance
“…Bacterioplankton communities are highly sensitive to changing aquatic environmental conditions [2,3] and are strongly influenced by water chemistry [4][5][6][7]. Today, water quality for many water bodies has deteriorated due to anthropogenic disturbances, such as industrial pollution [8], agricultural nonpoint source pollution [9], domestic sewage [10], residential areas. The number of daily visitors can reach 500-10,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterioplankton communities are highly sensitive to changing aquatic environmental conditions [2,3] and are strongly influenced by water chemistry [4][5][6][7]. Today, water quality for many water bodies has deteriorated due to anthropogenic disturbances, such as industrial pollution [8], agricultural nonpoint source pollution [9], domestic sewage [10], residential areas. The number of daily visitors can reach 500-10,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…Several past studies have reported the changes in the chemistry of river water mainly due to land use changes and terrace-agriculture practices (Jenkins et al 1995;France-Landlord et al 2003). In the present basin, during the recent past, a lot of land use and land cover conversions are taking place resulting in the spatial extents of agriculture land that is on a decline contrary to an increase in horticultural area Rashid and Romshoo 2012). The people, in order to coax more from the horticultural soil, add extra and different kinds of fertilizers, pesticides, insecticides, and fungicides.…”
Section: Temporal Variability Of Water Chemistrymentioning
confidence: 99%
“…Human activities have more or less impacts on the surrounding ecological environment, altering the nitrogen cycle in aquatic systems (Howarth et al 1996), changing hydrological circulation (Ahn and Merwade 2014), deteriorating river water quality (Rashid and Romshoo 2013;Liu et al 2014), etc. In a watershed scale, population growth significantly contributes to the pollutant concentrations in rivers and determines the carrying capacity of water environment to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid increase in the population is generally responsible for the degraded environment, particularly the aquatic ecosystem (Howarth et al 1996;Rashid and Romshoo 2013;Liu et al 2014). Rashid and Romshoo (2013) recognized the impacts of tourist numbers on seasonal variation in water quality of Lidder River in Kashmir Himalaya.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation